Diet of Arbuscular Mycorrhizal Fungi: Bread and Butter?. (August 2017) - Rich, Mélanie K.; Nouri, Eva; Courty, Pierre-Emmanuel; Reinhardt, Didier
Abstract : Most plants entertain mutualistic interactions known as arbuscular mycorrhiza (AM) with soil fungi ( Glomeromycota ) which provide them with mineral nutrients in exchange for reduced carbon from the plant. Mycorrhizal roots represent strong carbon sinks in which hexoses are transferred from the plant host to the fungus. However, most of the carbon in AM fungi is stored in the form of lipids. The absence of the type I fatty acid synthase (FAS-I) complex from the AM fungal model species Rhizophagus irregularis suggests that lipids may also have a role in nutrition of the fungal partner. This hypothesis is supported by the concerted induction of host genes involved in lipid metabolism. We explore the possible roles of lipids in the light of recent literature on AM symbiosis. Trends: AM fungi receive monosaccharides, in particular glucose, from the plant host. However, the fact that AM fungi lack FAS-I suggests that AM fungi may also receive lipidic nutrients. The coordinated induction in the host of genes involved in fatty acid and lipid biosynthesis provides further support to this idea. Thus, AM fungi may receive a complex diet from their hosts.